Pengaruh Ukuran Perusahaan, Reputasi Auditor dan Struktur Kepemilikan Terhadap Praktik Perataan Laba - Arsita Yanti, Ni Putu Dian; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi, 2016)
The purpose of this reseacrh is to obtain an empirical evidence from effect of firm size, auditor reputation, managerial ownership and public ownership to income smoothing practice. This reseach was carried out manufactur e company that listed in Indonesian Stock Exchange in perio d of year 2011-2014. This reseach used purposive sampling to collect the samples. Number of the sample used as many as 21 companies with 84 observation samples. The hypothesis tested using the Logistic Regressios Analysis. Based on Logistic Regression Analysis result, firm size, managerial ownership, and public ownership did not effect to income smoothing practice. Meanwhile the Auditor Reputation have a significant effect to income smoothing practice.
Keywords: Income Smoothing, Firm Size, Auditor Reputation, Ownership